Meningkatkan Hasil Belajar Siswa Melalui Metode Bermain Peran dengan Model Pembelajaran Cooperative Learning pada Pembelajaran Menjaga Keutuhan NKRI Kelas V SD Negeri 05 Limbanang Kecamatan Suliki - D, Masgeni (Jurusan PIPS FKIP UMMY Solok, 2018)
The purpose of this study was to improve the learning outcomes of fifth grade students of Limbanang Elementary School 05 through the application of role playing methods with Cooperative Learning models in learning the maintaining the integrity of the Republic of Indonesia. The problem in this study was the low learning outcomes of students in this topic. This type of research is Classroom Action Research (classroom action research) conducted in 2 cycles, each cycle consisting of 4 stages, namely planning, implementation, observation and reflection. Each cycle was held two meetings. The subjects of this study were the fifth grade students of Limbanang 05 Elementary School with 22 students which was consisting of 8 male students and 14 female students. In the first cycle of the first meeting of 22 students who took formative tests, there were still many students who were incomplete and meeting II there were 7 students (31.8%) that were not completed, this showed that the use of the experimental method had not been successful so reflection needed to be followed up. in cycle II. The implementation of learning in the second cycle of the teacher is more active in guiding and directing students in conducting experiments. Formative test results of cycle II meeting I were 22 students (100%) successfully completed. Based on the results of these studies it can be concluded that the use of experimental methods can improve the learning outcomes of fifth grade students of Limbanang Elementary School 05, Suliki District in PKN subjects.